Evaluation of Clinical Outcomes After Revascularization in Patients With Chronic Limb-Threatening Ischemia: Results From a Prospective National Cohort Study (RIVALUTANDO). (May 2021) - de Donato, Gianmarco; Benedetto, Filippo; Stilo, Francesco; Chiesa, Roberto; Palombo, Domenico; Pasqui, Edoardo; Panzano, Claudia; Pulli, Raffaele; Novali, Claudio; Silingardi, Roberto; Grego, Francesco; Palasciano, Giancarlo; et al.
We evaluated the outcomes of revascularization in patients with chronic limb-threatening ischemia (CLTI) treated in real-world settings. This is a prospective multicenter cohort study with 12-month follow-up enrolling patients (n = 287) with CLTI undergoing open, endovascular, or hybrid lower extremity revascularization. The primary end point was amputation-free survival (AFS) at 12 months. Cox proportional analysis was used to determine independent predictors of amputation and restenosis. At 30 days, major adverse cardiovascular and major adverse limb events (MALE) rates were 3.1% and 2.1%, respectively. At 1 year, the overall survival rate was 88.8%, the AFS was 86.6%, and the primary patency was 70.5%. Freedom from MALE was 62.5%. After multivariate analysis, smoking (hazard ratio [HR] = 2.2, P = 0.04), renal failure (HR = 2.3, P = 0.03), Rutherford class (≥5) (HR = 3.2, P = 0.01), and below-the-knee disease (HR = 2.0, P = 0.05) were significant predictors of amputation; iloprost infusion (>10 vials) (HR = 0.64, P = 0.05) was a significant protective factor. Cilostazol administration (HR = 0.77, P = 0.05) was a significant protective factor for restenosis. Results from this prospective multicenter registry offer a consistent overview of clinical outcomes of CLTI patients at 1 year when adequately revascularized. Medical treatment, including statins, cilostazol and iloprost, were associated with improved 1-year freedom from restenosis and amputation.